2015
DOI: 10.2119/molmed.2015.00056
|View full text |Cite
|
Sign up to set email alerts
|

Aloperine Protects Mice against Ischemia-Reperfusion (IR)-Induced Renal Injury by Regulating PI3K/AKT/mTOR Signaling and AP-1 Activity

Abstract: Aloperine is a quinolizidine alkaloid extracted from the leaves of Sophora plants. It has been recognized with the potential to treat inflammatory and allergic diseases as well as tumors. In this report, we demonstrate that pretreatment with aloperine provided protection for mice against ischemia-reperfusion (IR)-induced acute renal injury as manifested by the attenuated inflammatory infiltration, reduced tubular apoptosis, and well-preserved renal function. Mechanistic studies revealed that aloperine selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 66 publications
1
47
0
Order By: Relevance
“…Previous studies have shown that aloperine downregulates PI3K/Akt/mTOR signaling in HCT116 human colon cancer cells [ 10 ]. Our group confirmed that aloperine significantly attenuated ionizing radiation- (IR-) induced PI3K activation [ 11 ]. Aloperine is an alkaloid isolated from the shrub Sophora alopecuroides L. and has been recognized as an effective treatment for inflammatory and allergic diseases [ 11 17 ].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous studies have shown that aloperine downregulates PI3K/Akt/mTOR signaling in HCT116 human colon cancer cells [ 10 ]. Our group confirmed that aloperine significantly attenuated ionizing radiation- (IR-) induced PI3K activation [ 11 ]. Aloperine is an alkaloid isolated from the shrub Sophora alopecuroides L. and has been recognized as an effective treatment for inflammatory and allergic diseases [ 11 17 ].…”
Section: Introductionmentioning
confidence: 56%
“…Our group confirmed that aloperine significantly attenuated ionizing radiation- (IR-) induced PI3K activation [ 11 ]. Aloperine is an alkaloid isolated from the shrub Sophora alopecuroides L. and has been recognized as an effective treatment for inflammatory and allergic diseases [ 11 17 ]. It has been shown to increase CD4 + CD25 + cells and IL-10 levels as well as alleviate inflammation in mice with 2,4,6-trinitrobenzenesulfonic acid- (TNBS-) induced colitis [ 16 ].…”
Section: Introductionmentioning
confidence: 56%
“…The isolated islets and NIT-1 cells were stimulated with 2.5 mmol/l or 10 mmol/l STZ, respectively. ROS accumulation was analysed using 2′,7′dichlorodihydrofluorescein diacetate (DCFH-DA, 10 μmol/l; Beyotime, Shanghai, China) as previously described [26] (see ESM Methods).…”
Section: Analysis Of Ros Levelsmentioning
confidence: 99%
“…Analysis of NRF2 protein activity Chromatin immunoprecipitation (ChIP) assay [18], electrophoretic mobility shift assay (EMSA) [26] and dual-luciferase assay [18] were performed to analyse the activity of NRF2 (see ESM Methods).…”
Section: Analysis Of Ros Levelsmentioning
confidence: 99%
“…The sections were probed with primary antibodies against Aquaporin 1 (dilution 1:250; catalog number ab168387; Abcam, Cambridge, MA), VEGF-C (dilution 1:200; catalog number 22601-1-AP; Proteintech, Chicago, IL), F4/80 (dilution 1:50; MCA497RT; ABD Serotec, Oxford, UK), lymphatic vascular endothelial hyaluronan receptor 1 (LYVE-1; dilution 1:1000; ab14917; Abcam), CD45 (dilution 1:1000; GB11066; Goodbio Technology, Wuhan, China), CD4 (dilution 1:1500; GB11064; Goodbio Technology), CD8a (dilution 1:1500; Goodbio Technology), or myeloperoxidase (dilution 1:100; PA5-16672; Thermo Scientific, Waltham, MA) overnight at 4 C. The sections were then developed using a Vector stain ABC kit (Vector Laboratories Inc., Burlingame, CA) and further counterstained with Harris' hematoxylin as reported. 24 All sections were assessed under a microscope by two pathologists (Y.Z. and G.-C.P.)…”
Section: Histologic and Immunohistochemical Analysismentioning
confidence: 99%